The Safety and Efficiency of Percutaneous Nephrolithotomy in Managing Renal Stones in A Single Solitary Kidney - Faqed Faraj Almusawi (Diyala Journal of Medicine, 2024)
Background: Urologists have significant challenges when treating individuals with a solitary functional kidney who have renal stones. Various therapeutic approaches are employed to treat renal stones in people with just one working kidney, such as shock wave lithotripsy, retrograde intrarenal surgery, and percutaneous nephrolithotomy (PCNL). Objective: To assess the safety and efficiency of PCNL in patients with a solitary kidney. Patients and Methods: A percutaneous nephrolithotomy (PCNL) procedure was conducted on 20 patients who had a solitary kidney and were experiencing renal stone issues. The upper calyceal route was utilized. Factors such as the duration of the operation, full removal of the stone, presence of any remaining stone fragments, decrease in hemoglobin levels, requirement for a blood transfusion, necessity for any follow-up procedures, and length of hospital stay were all taken into account. Patients were monitored for a period of 6 months after the surgical procedure to identify any potential problems. Results: The mean age of the patients was 45.45±7.49 years (range: 34–61 years). About two-thirds of the patients (65%) were male. The mean stone size was 3.81 ± 1.57 cm. The mean operative time was 53.3±15.57 min (range: 30-90 min). Secondary puncture was required only in one case (5%). Residual stones were reported in 3 patients. Four patients (20%) needed blood transfusions. The mean duration of hospital stay was 36.3±16.51 hrs. Serum creatinine had dropped from 2.2±0.88 mg/dL preoperation to 1.54±0.31 mg/dL after 6 months postoperation, with a significant difference. Conclusion: PCNL is a safe and effective method for the removal of renal stones in patients with a solitary kidney, especially when other management options are not feasible. The procedure is associated with acceptable rate of residual stone, blood transfusion and postoperative hospital stay. Keywords: Solitary functional kidney, percutaneous nephrolithotomy, renal stone.